Optimization of LPG Distribution Using the Saving Matrix and Nearest Neighbor Methods - Fairuz Naila Qosammah; Ismail Husein (Journal of Computers and Digital Business, 2026)
The distribution of 3 kg LPG cylinders at UD. Tri Surya Efendi is currently conducted conventionally, without structured route planning, leading to fuel wastage, longer travel distances, and high operational costs. This research aims to determine the optimal distribution route by applying the Saving Matrix and Nearest Neighbor methods for 26 regular customers in the Helvetia–Marelan area with a total daily demand of 100 cylinders. Prior to optimization, customers were segmented into three geographic zones, and the distances between the depot and customer locations were obtained using Google Maps. The Saving Matrix method produced three routes spanning 28.06 km at a daily cost of Rp14,300, reducing operational costs by 64.25% compared to the initial Rp40,000. The Nearest Neighbor method produced four routes spanning 30.26 km at Rp15,130, reducing costs by 62.18%. The results show that the Saving Matrix method is more efficient in minimizing travel distance and distribution costs. This study contributes an empirical comparison of both methods in the context of small-scale LPG distribution with prior geographic zone segmentation, a procedure rarely documented in existing literature, and offers a practical reference for improving local distribution efficiency.